Formal Issues - Abe, Jair Minoro [UNESP]; Akama, Seiki; Nakamatsu, Kazumi; Abe, JM; Akama, S; Nakamatsu, K (Springer, 2015)
This chapter discusses formal issues of annotated logics. We describe an algebraic semantics for P tau based on Curry algebras. We also discuss annotated set theory, annotated model theory, proof methods, and annotated modal logics.